Global, regional, and national burden of schizophrenia: epidemiological trends, decomposition, joinpoint analysis, and projections to 2036 based on GBD 2021 - Zhou, Wanting; He, Jiujie; Wu, Lishuo; Wang, Liwen; Wu, Kejun; Li, Zongyu; Chen, Gang; Li, Donglian; Yang, Yi; Dai, Jian (Frontiers in Psychiatry, 2026)
BackgroundSchizophrenia continues to impose a substantial burden within the global spectrum of disease. This study utilizes the most recent data from the Global Burden of Disease Study 2021 (GBD 2021) to analyze epidemiological trends specific to schizophrenia and generate empirical evidence to guide the development of targeted prevention and clinical management strategies.MethodsLeveraging the GBD 2021 dataset, we examined age-standardized incidence, prevalence, and disability-adjusted life years (DALYs) for schizophrenia. We further evaluated temporal trends and age-sex-specific variations; executed decomposition analysis to identify primary determinants; conducted Joinpoint regression analysis; and generated projections through 2036.ResultsIn 2021, schizophrenia incidence demonstrated a declining trend, whereas prevalence and DALYs exhibited increasing trends. The burden disproportionately affected younger and middle-aged males, with a concomitant progressive increase observed among females. Significant disparities existed across geographic regions, high-SDI regions exhibited persistently elevated burden with upward trajectories, whereas low-SDI regions demonstrated progressive increases from lower baseline levels. These patterns were primarily attributable to population growth, SDI levels, and epidemiological parameter shifts, while population aging attenuated the schizophrenia burden.ConclusionsWhile schizophrenia currently exerts a disproportionately higher burden on young and middle-aged males, our projections indicate a notable epidemiological shift, with females expected to experience a steeper rise in incidence, prevalence, and DALYs over the next 15 years. This emerging female-centric trend contrasts sharply with the current male-dominated profile, underscoring the urgent need for sex-responsive mental health strategies.